The Physicochemical and Sensory Characteristics of Rice Noodle from Gelatinized Rice Flour with the Addition of Modified Cassava Starch, Carrageenan and Chitosan - Meiliena Meiliena; Elisa Julianti; Linda Masniary Lubis (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The aim of this research was to study the physicochemical and sensory characteristics of rice noodle which was made from the mixture of gelatinized rice flour, propionic acid modified cassava starch, carrageenan as emulsifier and chitosan as natural preservative. The manufacture of composite flour from gelatinized rice flour and modified cassava starch in 4:1 ratio plus carrageenan (0, 10, 20, and 30%) and chitosan (0,1, and 2%) and then used for making rice noodle. The result showed that the correlation between carrageenan’s and chitosan’s concentration showed highly significant difference on ash and crude fiber content,  also on flavor and texture of rice noodle. The best quality of rice noodle was made from composite flour – gelatinized rice flour and modified cassava starch and the addition of  2% chitosan and 0% carrageenan. Keywords: Rice noodle, Gelatinized Rice Noodle, Carrageenan, Chitosan, Propionic Acid Modified Cassava Starch